The new (dis)order in RNA regulation. Issue 1 (December 2016) - Järvelin, Aino; Noerenberg, Marko; Davis, Ilan; Castello, Alfredo
Abstract RNA-binding proteins play a key role in the regulation of all aspects of RNA metabolism, from the synthesis of RNA to its decay. Protein-RNA interactions have been thought to be mostly mediated by canonical RNA-binding domains that form stable secondary and tertiary structures. However, a number of pioneering studies over the past decades, together with recent proteome-wide data, have challenged this view, revealing surprising roles for intrinsically disordered protein regions in RNA binding. Here, we discuss how disordered protein regions can mediate protein-RNA interactions, conceptually grouping these regions into RS-rich, RG-rich, and other basic sequences, that can mediate both specific and non-specific interactions with RNA. Disordered regions can also influence RNA metabolism through protein aggregation and hydrogel formation. Importantly, protein-RNA interactions mediated by disordered regions can influence nearly all aspects of co- and post-transcriptional RNA processes and, consequently, their disruption can cause disease. Despite growing interest in disordered protein regions and their roles in RNA biology, their mechanisms of binding, regulation, and physiological consequences remain poorly understood. In the coming years, the study of these unorthodox interactions will yield important insights into RNA regulation in cellular homeostasis and disease.